Iluminasi Manuskrip Kanjeng Kyai Al Qur'an: Perpaduan Seni Islam dan Tradisi Jawa dalam Warisan Budaya - Sartono, Dedy; Mahardhika, Cholis; Pahlawan, Reza; Rizki Amalia, Danti (EduInovasi: Journal of Basic Educational Studies, 2025)
This study examines the illumination of the Kanjeng Kyai Al Qur'an manuscript, an ancient Quranic manuscript completed in 1799 in Surakarta, now preserved at the Yogyakarta Hadiningrat Palace. As a religious text and a work of art, this manuscript reflects the artistic skills and spirituality of the Yogyakarta community in the 18th century. The research explores the fusion of Islamic art styles, such as arabesques and geometric motifs, with traditional Javanese elements rich in philosophical symbolism. Through a qualitative descriptive approach, this study maps the historical context, illumination techniques, and materials used in the manuscript's creation, as well as its relevance to art education and the character of the Yogyakarta community. Findings indicate that the illumination of this manuscript integrates aesthetics, symbolism, and spiritual values, making it a source of inspiration for contemporary art and a medium for cultural heritage preservation. The implications of this research include enriching the art education curriculum, fostering character development based on local values, and strengthening cultural identity in the era of globalization. Keywords: Character Education, Illumination, Islamic Art, Islamic Art, Javanese Tradition, Manuscript